Impact of the Metal Center and Leaving Group on the Anticancer Activity of Organometallic Complexes of Pyridine-2-carbothioamide - Jahanzaib Arshad; Kelvin K. H. Tong; Sanam Movassaghi; Tilo Söhnel; Stephen M. F. Jamieson; Muhammad Hanif; Christian G. Hartinger (Molecules, 2021)
RuII(cym)Cl (cym = η6-p-cymene) complexes of pyridinecarbothioamides have shown potential for development as orally active anticancer metallodrugs, underlined by their high selectivity towards plectin as the molecular target. In order to investigate the impact of the metal center on the anticancer activity and their physicochemical properties, the Os(cym), Rh- and Ir(Cp*) (Cp* = pentamethylcyclopentadienyl) analogues of the most promising and orally active compound plecstatin 2 were prepared and characterized by spectroscopic techniques and X-ray diffraction analysis. Dissolution in aqueous medium results in quick ligand exchange reactions; however, over time no further changes in the 1H NMR spectra were observed. The Rh- and Ir(Cp*) complexes were investigated for their reactions with amino acids, and while they reacted with Cys, no reaction with His was observed. Studies on the in vitro anticancer activity identified the Ru derivatives as the most potent, independent of their halido leaving group, while the Rh derivative was more active than the Ir analogue. This demonstrates that the metal center has a significant impact on the anticancer activity of the compound class.